Motivating Management to Reveal Inside Information - TRUEMAN, BRETT (Journal of Finance, 1983)
ABSTRACT This paper develops incentive schemes which motivate a manager to release private information that he has concerning the probabilities of occurrence of the various output levels of his firm. It is shown that, in the context of a pure‐exchange economy, a complete prohibition on the manager's trading in his firm's stock is sufficient to motivate him to truthfully release his private information. When the setting is extended to that of a production‐exchange economy, the manager must also be allowed to choose the production plan that he most prefers in order for him to be motivated to release his information truthfully. In fact, no incentive scheme in a general production‐exchange economy can be guaranteed to motivate the manager to release his information truthfully if he is not allowed to choose the production plan freely. However, when more structure is placed on the economy, such an incentive scheme can be developed as described in the latter part of this paper.